Criminal Liability of Children in Online Gambling Promotion and the Restorative Approach - BANI, Feny Nursya; FAHREIN, Shenna Ismi; BHAKTI, Tegar Yuda (Journal of Political And Legal Sovereignty, 2024)
Purpose:The phenomenon of increasing involvement of children in online gambling promotion raises a complex legal dilemma, especially regarding the balance between protecting children's rights and providing criminal accountability. This study examines the effectiveness of the juvenile criminal justice system in Indonesia in handling online gambling promotion cases and assesses the urgency of implementing a restorative approach as a fairer and more recovery-oriented alternative.Methodology:The restorative approach emphasizes restoring relationships between perpetrators, victims, and the community, so as to avoid stigmatization and provide opportunities for children to improve their behavior.Findings:The results of this study confirm that the legal system must prioritize the principle of rehabilitation rather than punishment alone, in order to ensure the protection of children while preventing the recurrence of criminal acts.Implication:Thus, the application of restorative justice in cases of children involved in online gambling promotion is a strategic step to create a more humane and future-oriented justice system.